Dreams of Teeth Falling Out: An Empirical Investigation of Physiological and Psychological Correlates - Rozen, Naama; Soffer-Dudek, Nirit (Frontiers in Psychology, 2018)
Teeth dreams (TD), i.e., dreams of teeth falling out or rotting, are one of the most common and universal typical dream themes, yet their source remains unknown and they have rarely been studied empirically. They are especially enigmatic as they do not readily fall under the rubric of the “continuity hypothesis”, i.e., dreams of current and salient waking-life experiences. The aim of the present study was to explore two possible hypotheses for the origin of TD; specifically, TD as incorporation of dental irritation into dreaming, and TD as a symbolic manifestation of psychological distress. Dream themes, dental irritation, psychological distress, and sleep quality were assessed among 210 undergraduates. TD were related to dental irritation (specifically, tension sensations in the teeth, gums, or jaws upon awakening), whereas other dream types were not. Conversely, TD were unrelated to psychological distress, whereas other dream types were (specifically, dreams of being smothered and dreams of falling). This disparity in the correlates of TD existed despite a small but significant relationship between psychological distress and dental irritation. Albeit preliminary, the present findings support the dental irritation hypothesis and do not support the symbolic hypothesis regarding the origins of TD. Research on TD portrays one path through which the mind may distort somatosensory stimuli and incorporate them into dreams as a vivid and emotionally-salient image; these preliminary findings highlight the potential of studying TD in order to broaden our understanding of the cognitive mechanisms governing dream production.